2015
DOI: 10.1039/c4tc02737j
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-tunable PDMS microlens fabricated by femtosecond laser direct writing

Abstract: Reported here is the fabrication of a solvent-tunable polydimethylsiloxane (PDMS) microlens using the femtosecond laser direct writing (FsLDW) technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 35 publications
0
46
0
Order By: Relevance
“…[6,7] Self-assembly approaches to 3D periodic structures (using colloidal spheres immersed in liquids or embedded in polymers [8,9] ) have shown significant promise for tuneable color and strain sensing. However, direct write fabrication brings the flexibility to engineer arbitrary structures such as tuneable lenses, [10,11] and produce a series of 2D and 3D tuneable optical systems that are optically active over a wide wavelength range. [12][13][14][15] Currently, many routes to tuneable optical systems exploit mechanisms such as swelling of the optical material, [3,10] thermally controlled dimensional changes, [5] or interaction between solvents and optical structures.…”
Section: Doi: 101002/adom201600458mentioning
confidence: 99%
See 2 more Smart Citations
“…[6,7] Self-assembly approaches to 3D periodic structures (using colloidal spheres immersed in liquids or embedded in polymers [8,9] ) have shown significant promise for tuneable color and strain sensing. However, direct write fabrication brings the flexibility to engineer arbitrary structures such as tuneable lenses, [10,11] and produce a series of 2D and 3D tuneable optical systems that are optically active over a wide wavelength range. [12][13][14][15] Currently, many routes to tuneable optical systems exploit mechanisms such as swelling of the optical material, [3,10] thermally controlled dimensional changes, [5] or interaction between solvents and optical structures.…”
Section: Doi: 101002/adom201600458mentioning
confidence: 99%
“…However, direct write fabrication brings the flexibility to engineer arbitrary structures such as tuneable lenses, [10,11] and produce a series of 2D and 3D tuneable optical systems that are optically active over a wide wavelength range. [12][13][14][15] Currently, many routes to tuneable optical systems exploit mechanisms such as swelling of the optical material, [3,10] thermally controlled dimensional changes, [5] or interaction between solvents and optical structures. [7,10] The focus of this study is on using materials that undergo refractive index changes (and tuning), induced by a chemical reaction that transfers the materials from a dielectric to a conducting state.…”
Section: Doi: 101002/adom201600458mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, D. Lu et al reported the fabrication of femtosecond laser direct writing (FsLDW) technology and in-situ integrated PDMS microlenses such as spherical microlenses and aspheric hyperbolic microlenses. Optical focusing tests were performed using PDMS hyperboloid microlenses with a radius of 20 μm, a height of 3.5 μm, and a theoretical focal length of 117 μm[148]…”
mentioning
confidence: 99%
“…Yong et al fabricated a low-cost, high-quality, concave PDMS micro-lens array using high-speed line-scanning of femtosecond laser pulses [21]. Lu et al reported the fabrication of solvent-tunable PDMS micro-lenses using a femtosecond laser direct writing technique through a multi-photon absorption process [22]. Stankova et al presented an experimental investigation on the effects of process parameters on a medical grade PDMS elastomer processed by a laser source [23].…”
Section: Introductionmentioning
confidence: 99%